Lean Six Sigma Approach for Simultaneous Quality Improvement of Courses in Higher Education Institutions During Covid-19 Pandemic - Govindhankutty, Jayamohan K.; Balakrishnan, Bhasi A. (UUM Press, 2024)
The purpose of this study is to assess whether Lean Six Sigma can improve the quality of teaching-learning processes in hgher educational institutions during the Covid-19 pandemic. The integration of e-learning technologies with lean six sigma (LSS). DMAIC stands for five phases of sig sigma project: define, measure, analyze, improve, and control was applied to implement quality assurance in the teaching-learning process. Action research was adopted in 30 courses of a particular engineering programme. The methodology was applied as a course improvement tool, and the challenges encountered during the implementation were also studied. The LSS DMAIC methodology could successfully improve the quality of various courses simultaneously through online mode during the Covid-19 pandemic. The adopted methodology could assist in effectively responding during the present stage of uncertainty and provide stakeholders with guidelines to deal with the post-pandemic era. In terms of practical implications, this study discusses a new approach to improving the quality of the teaching-learning process in higher educational institutions. The LSS DMAIC is applied with the help of online educational and social media platforms for the simultaneous improvement of courses in a particular engineering programme